Strategi Meningkatkan Profesionalisme Guru Pendidikan Agama Islam Melalui Program Guru Penggerak Di MTs Negeri 1 Langkat - Yasmi Amelia, Usmaidar, Zaifatur Ridha (Pusdikra Publishing, 2023)
Based on the results of observations made by the author at MTs Negeri 1 Langkat, the following information was obtained: The mobilization teacher program has been implemented in madrasahs, however, the mobilization teacher program is still new, so it is stagnant at the training, mentoring and habituation program stages to provide access to teachers in practice their abilities as a learning mover. The driving teacher program makes teachers have the basic skills and abilities to manage Emotional Quality (EQ) so that teachers will play an active role in improving students' talents and competencies. The application of driving teachers at MTs Negeri 1 Langkat is still focused on Islamic Religious Education teachers, namely teachers in the fields of Islamic Religious Education, Islamic Cultural History, Arabic Language, Fiqh and Akhlak. So that the strategy to increase the professionalism of driving teachers only focuses on Islamic Religious Education but does not lead to other general learning. Based on the background of these problems, the researchers carried out research with a qualitative research model, namely using observation, interview and documentation techniques. As for the results of the implementation of this research, it can be concluded that the strategy to increase the professionalism of Islamic religious education teachers can be carried out through a teacher mobilization program so that it can influence the quality of education and the quality of teaching staff at MTs Negeri 1 Langkat.